THE EFFECT OF ECONOMIC GROWTH ON THE NUMBER OF POOR POPULATIONS - Marlina, Sitti; Musdalifah, Musdalifah; Nasruddin, Nurfitraeny (Yayasan Education and Social Center, 2023)
Poverty has become an interesting discussion and study for many people. Basically, research on poverty highlights on how the problem roots and solutions that can be used to minimize poverty. The purpose of this study was to determine the effect of economic growth on the number of poor people in the province of South Sulawesi. This study uses a quantitative research approach using data collection techniques through documentation. The population in this study is time series data related to economic growth and the number of poor people in South Sulawesi Province from 2000-2013. This research used regression analysis and hypothesis testing. The results of this study showed that there is a significant effect of economic growth on the number of poor people in South Sulawesi Province